A Review of Islamic Family Law Regarding Divorce Cases Arising from Infidelity in the Digital Sphere: Kajian Hukum Keluarga Islam Mengenai Kasus Perceraian Akibat Perselingkuhan di Ranah Digital - Pamela Pramidya; Lilik Andaryuni (Institut Agama Islam Negeri Fattahul Muluk Papua, 2026)
The increasing use of digital communication technology and social media has transformed marital interactions and contributed to the emergence of infidelity in the digital sphere, creating new challenges for family relationships and legal systems. This study aims to analyze digital infidelity as grounds for divorce from the perspective of Islamic family law and its relevance within the Indonesian legal system. This research employs a normative legal research method using statute and conceptual approaches. Data were collected through library research involving legislation, the Compilation of Islamic Law, classical Islamic jurisprudence literature, books, and scholarly journals related to digital infidelity and Islamic family law. The findings reveal that digital infidelity contradicts the principles of loyalty and marital harmony in Islam, even though it does not always involve direct physical relationships. In the practice of Religious Courts in Indonesia, digital infidelity may serve as grounds for divorce under the category of continuous disputes and marital conflicts supported by electronic evidence. The findings further highlight the importance of legal reform in Islamic family law to respond more effectively to the challenges of the digital era through the maqāṣid al-sharī‘ah approach and strengthened regulations concerning electronic evidence in divorce cases.